Juridical Analysis of Debt Settlement Through Bankruptcy (Study of Decision 24/Pdt.Sus-Bankrupt/2019/PN Niaga Sby) - Tiyas Asri Putri; Gusnardi Lie; Moody Rizqy Syailendra Putra (CV. Rayyan Dwi Bharata, 2023)
Every bankruptcy has legal consequences for both the debtor and the creditor, one of which is the ability to represent the bankrupt debtor in property law matters. As a result, the authority of the debtor is very limited. Therefore, the debtor remains liable for outstanding debts in the event of bankruptcy, and the creditor must use all reasonable efforts to collect outstanding debts. Regarding debt settlement through bankruptcy (Decision of the Surabaya District Court Case PT. Sinar Pembangunan Abadi) to find out the basis for the considerations of the Panel of Judges in case number: 24/Pdt.Sus-Pailit/2019. This case was originally with the bankruptcy respondent having debts to the bankruptcy applicants that were due and could be collected for severance/compensation payments. This study uses the method of literature review. This type of research data is secondary data. The normative approach to analyzing juridical legal analysis is to resolve issues related to debt settlement difficulties in the consideration that the Commercial Court at the Surabaya District Court has stated that it is proven that it has not fulfilled the legal or debt obligations mentioned above, then the legal consequences (legal consequences) of the bankruptcy respondent can be declared negligent law (ingebreke stelling) can be declared negligent or default on their obligations (counter-performance) in accordance with the provisions of Article 1238 of the Civil Code.